Breastfeeding awareness - Muda, Siti Mariam (IIUM Press International Islamic University Malaysia, 2018)
Islam recommends breastfeeding and greatly emphasized in the various Quranic verses. There are issues related to breastfeed are stated eight times in the Holy Quran. According to the World Health Organisation (WHO), infants should be fed exclusively on breast milk until they reach six month of life. The targeted is to become healthy and achieve optimal growth and development. WHO also actively promotes breastfeeding as the best source of nourishment for infants and young children. WHO and UNICEF recommend: early initiation of breastfeeding within 1 hour of birth; exclusive breastfeeding for the first 6 months of life; and introduction of nutritionally adequate and safe complementary (solid) foods at 6 months together with continued breastfeeding up to 2 years of age or beyond (WHO, 2017).The ‘Ten Steps for Successful Breastfeeding’ serves as the golden standard for achieving the BFHI status. The 10 steps are as follows: 1. To have a written policy on breastfeeding 2. To equip all health care staff with knowledge and skill on breastfeeding, 3. All pregnant women should be well-informed on the benefits of breastfeeding 4. To help mothers to initiate breastfeeding within half an hour of delivery 5. To show mothers how to breastfeed even separated from their infants 6. Newborns should receive breast milk only unless it is otherwise indicated medically 7. To practice rooming-in 8. To encourage breastfeeding on demand 9. To avoid artificial teats or pacifiers to breastfeeding infants 10. To foster the establishment of breastfeeding support